Hans Peter Mareus Neilsen Gammel, The Laws of Texas, 1822-1897. Austin’s Colonization Law and Contract; Mexican Constitution of 1824; Federal Colonization Law; Colonization Laws of Coahuila and Texas; Colonization Law of State of Tamaulipas; Fredonian Declaration of Independence; Laws and Decrees, with Constitution of Coahuila and Texas; San Felipe Convention; Journals of the Consultation; Proceedings of the General Council; Goliad Declaration of Independence; Journals of the Convention at Washington; Ordinances and Decrees of the Consultation; Declaration of Independence; Constitution of the Republic; Laws, General and Special, of the Republic; Annexation Resolution of the United Sates; Ratification of the same by Texas; Constitution of the United States; Constitutions of the State of Texas, with All the Laws, General and Special passed thereunder, Including Ordinances, Decrees, and Resolutions, with the Constitution of the Confederate States and the Reconstruction Acts of Congress., at 1140, An Act Amendatory of an Act to punish certain offences committed on Sunday, § 3 (Vol. 5, 1898) - (:unkn) unknown (General Publisher, 1863)
That any person or persons who shall engage in hunting game, either with gun or dogs, or otherwise, on Sunday, shall be deemed guilty of a misdemeanor, and upon conviction, shall be fined not less than five nor more than twenty-five dollars
--
Keywords: HUNTING REGULATION